Lecturer and Student Satisfaction with the Quality of Management Services at the Learning and Professional Development Institute (LP3) State University of Surabaya - Meirinawati, Meirinawati; Nuryono, Wiryo; Surhatiningsih, Surhatiningsih; Wismanadi, Himawan (Universitas Negeri Surabaya, 2023)
This research was conducted at UNESA, more specifically the Institute for Learning and Professional Development (LP3). Especially those related to the services available to related parties, namely Unesa lecturers and students. Based on Circular B/15254 /[IN38 / TU.00.021/ 2020] issued by the Chancellor of Unesa regarding the steps to prevent the spread of the coronavirus Deseas19 (COVID19) at the State University of Surabaya which stipulates that practical activities will be carried out online from March 16, 2020 until with the next decision. Therefore, this research was conducted online using a descriptive correlational approach. Specifically, the purpose of this research is to determine the following: 1) The satisfaction (recognition) of lecturers and students towards the quality of LP3 management services. 2) Quality of LP3 management performance and 3) Relationship between service quality and lecturer-student satisfaction. The method used is descriptive and consists of preparation. It starts with editing online, effective and reliable tools to measure service quality and teacher and student satisfaction, and then collects and analyzes data online using surveys in the form of Google Forms. Descriptive data analysis and correlation. The results of this survey can be used as discussion material for improving the quality of online services. In addition, you can find the barriers and obstacles experienced by lecturers and students.